Sensory evaluation, physicochemical analysis, and glycaemic index of sweet potato (ipomoea batatas) flour composited doughnuts - Khairunnisa, Kamarudin; Napisah, Hussin; Zarinah, Zakaria (2019)
Background and Aims : Muffins are one of bakery product that been consumed as snack widely by all aged. Wheat flours are being used as the basic ingredient of muffin and may have limited amount of nutritive value as compared to the pumpkin flour. The general objective of this study is to determine the sensory acceptance, physicochemical characteristic and expected glycaemic index of the wheat muffin incorporated with pumpkin flour. Materials and Methods : The pumpkin flour was prepared and assessed for proximate properties and was used in the muffin formulation. The muffins were prepared by substituting the wheat flour with pumpkin flour at different percentage (10%, 20%, 30%, 40% and 50%). The muffin was then being assessed for sensory evaluation and the three most preferred muffins were chosen for physicochemical analysis and expected glycaemic index. Results : The results showed that pumpkin flour contain 74.8% carbohydrate, 0.7% fat, 7.4% protein, 12.8% moisture, 4.0% ash and 0.3% fiber. The substitution of pumpkin flour effects the result in sensory evaluation, as the most preferred muffins with incorporated pumpkin flour were at 30%, 40% and 50%. It shows that increasing in the volume led to decreased in firmness and springiness of the muffin. The nutritive value of the wheat muffin incorporated with pumpkin flour was increased, but expected glycaemic index of incorporated muffin were decrease up to 15.4% compared to the control muffin. Conclusion : In conclusion, by adding pumpkin flour into the muffin, it can increase the sensory acceptance of the muffin, volume and the nutritive value of the muffin but decrease the value of expected glycaemic index of the incorporated muffin.